Improving Writing Skill Using Chain Sentences on the First Semester Students' at Universitas Bhinneka PGRI Tulungagung - Ika Rakhmawati (STKIP PGRI Tulungagung, 2022)
English learner has to master four skills namely listening, speaking, reading and writing. Writing is considered as the important skill in linguistic. The students write the idea based on their mind in the written form. The students of the first semester have many difficulties in writing English. They do not know the pattern of the sentence properly. They do not master vocabulary and grammar. The important thing is English grammar which is very hard to be mastered by the students. The teacher should apply the appropriate method in conducting teaching and learning process in writing skill. Chain Sentences learning model is also a learning model that can be used Lecturer to change the atmosphere of learning in the classroom with more fun, so that students feel more interested. Because in this Chain Sentences learning model, this activity should be done in groups where when the first person has listened to the lecturers' sentence then, make a sentence from the last word of the first sentence becomes the first word of the second sentence, as well as the second student and so on. Based on the students’ score on preliminary study, it is shown that the students’ writing needed improvement caused their scores were low. There were 59,52% of 25 students who passed the writing test. The success of this class was less than 80%. The result could not achieve the criteria of success. It means that the students’ writing before the implementation of the strategy is quite weak. To improve the students’ writing, the researcher did this classroom action research. From first cycle, it is known that amount of the students who passed the vocabulary test increased. The result of the study on this cycle was 36 students passed the writing test. 82.71% of the students were successful and it had achieved the criteria of success. It means that the students’ writing skill improved after the strategy